Perancangan Sistem Pendukung Keputusan Untuk Seleksi Siswa Non-Akademik Cabang FLS3N di SMA Negeri 2 Muaro Jambi dengan Metode Topsis - Ayu Anggelina; Fachruddin Fachruddin; Jasmir Jasmir (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The National Student Arts Festival and Competition (FLS3N) is an event aimed at developing students’ talents and achievements in the arts, including solo vocal competitions. The assessment process in this category involves multiple criteria, which may lead to subjectivity in decision-making. This study aims to design and develop a web-based Decision Support System (DSS) for selecting non-academic students in the FLS3N solo vocal category using the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method. The assessment criteria are based on the 2025 FLS3N Technical Guidelines, consisting of voice quality, vocal technique, expression, and performance. The TOPSIS method is applied to generate alternative rankings based on the highest preference value. The system is developed using a web-based software development approach and tested using participant data from both male and female categories. The results indicate that the system can provide objective and consistent ranking recommendations, thereby assisting schools in selecting the best students to represent them in the FLS3N competition.